Ganti Rugi Tanah di Ibu Kota Nusantara: Tinjauan Hukum dan Kendala Pengadaan - Wijaya, Hendra; Pranata, Andri (International Journal of Politic, Public Policy and Environmental Issues, 2024)
Land acquisition for public interest in the Nusantara Capital City (IKN) is a complex legal issue, particularly concerning compensation for communities affected by land acquisition. This study aims to analyze the mechanism of land compensation, especially for communities without land certificates, and to identify the obstacles faced by the government in the land acquisition process. The research method employed is normative legal research, utilizing literature and field data approaches. The findings indicate that although communities without land certificates are still entitled to compensation, various obstacles exist, such as uncertainty in land ownership and resistance to the proposed compensation amounts. Additionally, the land acquisition process is often hindered by administrative issues and a lack of public understanding regarding their rights. This study recommends enhancing socialization and transparency in the land acquisition process, as well as a review of compensation policies to ensure fairness and adequacy for all affected parties.